PERANCANGAN HOTEL LIMA BELAS LANTAI DI BANJARMASIN - Bengawan L. Kosasih (INFO-TEKNIK, 2014)
Multy story building  is a building that has more than one floor. The higher the more complicated calculation of construction. In this final project, entitled "Design of Fifteen Story Building Hotel in Banjarmasin" aims to produce multi-story building are safe and can function as it should.            The building is divided into super structures and substructure. Calculation of the structural design analysis is aided by the program SAP 2000. For the upper structure calculation using the rules of SNI 2002. And for the calculation of the foundation is using the Pile Capacity of Static Cone Test method.            From the design result dimensions of the primary beam B1 (35/70), B2 (37,50/75), B3 (50/100) 30/40 and dimensions of the secondary beam B4 (35/65), B5 (35/65), B6 (35/65), and B7 (35/70) with thickness of slabs is 150 mm. Whereas, dimension of the primary beam at dak is 30/45 and 25/40 for secondary beam with thickness of slabs is 150 mm. The thickness of shearwall is 35 mm The diameter of pile foundation is used in this building is 70 cm with a length of 38 meters. The foundation is divided into 4 types where each type has a number of piles as much as 11 to 22 piles. Keywords:  pile foundations, SAP 2000, Pile Capacity of Static Cone Test method